Spring-summer climatological circulation in the upper layer in the region of Cape St. Vincent, Southwest Portugal - Sanchez, R. F. (2018)
Geostrophic transport and hydrographic measurements derived from a historical database (1900-1998) were used to study the spring-summer mean circulation in the upper layer south and west of Cape St. Vincent, Southwest (SW) Portugal. The larger-scale circulation scheme is forced by equatorward winds from May to September, when the Iberian coastal transition zone (CTZ) is dominated by a generalized upwelling of cold, low-salinity water. A partially separated surface jet intensified at the shelf break conveys similar to1 Sv of upwelled water equatorward parallel to the bathymetry, while offshore a poleward flow transports similar to0.4-0.6 Sv of upwelled water. Although alongshore transports dominate the circulation pattern of the upper layers, cross-shore transports are significant at the climatological scale. Anticyclonic circulation with an exchange of similar to0.5 Sv from the equatorward jet to the offshore poleward flow and the partial re-circulation further north, back into the equatorward flow are discussed. A coherent, cyclonic re-circulation pattern inshore of the upwelling jet is also speculated. From these results the shelf break is considered a climatological border at both sides of which two major re-circulation cells occur. The climatological equatorward flow has offshore protrusions, interpreted as recurrent episodes of major contortions of the upwelling flow. These features bring about considerable "cross-shelf flow" re-circulation reaching up to 50% of the main flow. The most significant exchanges are found to be associated with major changes of orientation of the coastline. Off Cape St. Vincent the upwelling front stretches to both west and south and contributes to the cross-shelf re-circulations. Additionally, convergence of the upwelling flow and a branch of the Azores current, with associated re-circulation is found diagonally from the cape. On the southern coast the upwelling jet is seen to meander offshore in the vicinity of Cape St. Maria. Individual synoptic cruise data showed agreement with the climatological circulation features. We conclude that these oceanographic features leave an imprint on the climatic circulation in spite of the "smoothing out" of recurrent events over the spring-summer period of the years of 1900-1998. (C) 2003 International Council for the Exploration of the Sea. Published by Elsevier Ltd. All rights reserved.